Blocking properdin, the alternative pathway and anaphylatoxin receptors ameliorates renal ischemia reperfusion injury in decay-accelerating factor and CD59 double knockout mice() - Miwa, Takashi (2013)
Complement is implicated in the pathogenesis of ischemia reperfusion injury (IRI). The activation pathway(s) and effectors(s) of complement in IRI may be organ-specific and remain to be fully characterized. We previously developed a renal IRI model in decay-accelerating factor (DAF) and CD59 double knockout (DAF(−/−)CD59(−/−)) mice. Here we used this model to dissect the pathway(s) by which complement is activated in renal IRI and to evaluate whether C3a or C5a receptor (C3aR, C5aR)-mediated inflammation or the membrane attack complex (MAC) was pathogenic. We crossed DAF(−/−)CD59(−/−) mice with mice deficient in various complement components or receptors including C3, C4, factor B (fB), factor properdin (fP), mannose-binding lectin (MBL), C3aR and C5aR or immunoglobulin (Ig) and assessed renal IRI in the resulting mutant strains. We found that deletion of C3, fB, fP, C3aR or C5aR significantly ameliorated renal IRI in DAF(−/−)CD59(−/−) mice, whereas deficiency of C4, Ig, or MBL had no effect. Treatment of DAF(−/−)CD59(−/−) mice with an anti-C5 mAb reduced renal IRI to a greater degree than C5aR deficiency. We also generated and tested a function-blocking anti-mouse fP mAb and showed it to ameliorate renal IRI when given to DAF(−/−)CD59(−/−) mice 24 hr before, but not 4 or 8 hrs after, ischemia/reperfusion. These results suggest that complement is activated via the alternative pathway during the early phase of reperfusion and both anaphylatoxin-mediated inflammation and the MAC contribute to tissue injury. Further, they demonstrate a critical role of properdin and support its therapeutic targeting in renal IRI.